Language Politics in Nepal - Dahal, Ram Kumar (Journal of Political Science, 1998)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Journal of Political Science Vol.1(1) 1998 p.51-71